Precision Augmentation of Medical Surge Capacity for Disaster Response. (16th March 2020) - Shen, Weifeng; Jiang, Libing; He, Xiaojun
Abstract : Background . In recent years, serious injuries associated with extreme climate, earthquakes, terrorism, and other natural and man-made disasters have occurred frequently throughout the world. A surge in medical demand that extends beyond local medical surge capacity in mass casualty incidents following major disasters is common. Materials and Methods . We reviewed and analyzed emergency medical rescue efforts after major disasters in recent years to elaborate the precision strategy of augmenting medical surge capacity for disaster response. Results . Precision augmentation of medical surge capacity for disaster response can be achieved through several measures. These include (1) release of internal capacity through precision launching or through upgrading the levels of response, (2) precision support for medical surge capacity from external efforts, (3) centralized response, and (4) altering standards of care. We should adopt precision augmentation of medical surge capacity according to the specific situation. Conclusions . Augmentation of medical surge capacity as a basic strategy can be used to achieve effective disaster response. In disaster response, due to the complexity of disaster medical capacity amplification, it is important to select the appropriate medical capacity strategy accurately according to the actual disaster situation.